Вплив соціальних факторів на реалізацію принципу поділу влади: історико-правовий аспект - Колесниченко, Н.; Kolesnychenko, N.; Юхимюк, О.; Yukhymiuk, O. (Східноєвропейський національний університет імені Лесі Українки, 2019)
Стаття присвячена аналізу впливу різноманітних соціальних явищ, зокрема потрясінь, таких як війни, революції та перевороти, на теорію поділу державної влади та принципу стримувань і противаг, форми недотримання цих принципів, виникнення цих форм та їх наслідки. Автори спрогнозувалм, що у майбутньому можливий відхід від системи поділу влади та стримувань і противаг, якщо суспільство зможе і захоче пожертвувати своїми свободами заради вирішення основних соціальних проблем. В такому разі можливе виникнення поляризації: держави із «м’яким» поділом влади відкинуть його, а із «жорстким» – ще більше вкорінять цю систему у своїй формі. The article is devoted to the analysis of the impact of various social phenomena, in particular shocking events (wars, revolts and revolutions) on the theory of separation of state powers and the principle of checks and balances. In the focus of the study are the forms of non-compliance with these principles, the emergence of these forms and their consequences. The ideas of the division of state power and the system of checks and balances were formed in human consciousness in the ancient times and were reflected in the constitutions of the New-Age states but still remain topical. Their efficiency drops sharply in proportion to the seriousness of social upheavals. To reach a higher level of viability in times of crisis, the state must either ignore the division of state power or put it into practice as «rigid». Although efficiency does not always depend on this system, it nevertheless is one of the most prominent and most crucial in the concept of «state form». Taking into account the cyclicality of both the state and social development of the world, the authors predict a possible departure from the system of separation of powers and checks and balances, if a society can and wants to sacrifice its freedoms to solve the basic social problems in the future. In this case, polarization may occur: states with a «soft» division will discard it, and those with a «rigid» one will further consolidate this system in their own way.
Influence of the Social Factors on the Implementation of the Principle of Separation of Powers: the Historical and Legal Aspects
Keywords: держава; принцип поділу державної влади; система стримувань і противаг; state; principle of division of state power; system of checks and balances